Inclusive Entrepreneurship and Sustainable Development in the Special Region of Yogyakarta: A Conceptual Study from the Perspective of Community Empowerment - Alamsyah Agit; Oktavianty (International Journal Business and Entrepreneurship, 2026)
Inclusive entrepreneurship has developed as a strategic approach to addressing social and economic disparities by expanding access to entrepreneurial opportunities for marginalized groups. This study aims to conceptualize how inclusive entrepreneurship can be utilized as a pathway toward sustainable regional development in the Special Region of Yogyakarta, with a focus on community empowerment. Through a conceptual review based on a systematic selection of scientific publications from the past decade, this research synthesizes theoretical and empirical findings related to inclusive entrepreneurship, sustainable development, and local empowerment strategies. The analysis results show that inclusive entrepreneurship makes a significant contribution to improving local livelihoods by creating jobs, reducing income inequality, and encouraging grassroots innovation. Empowerment initiatives such as participatory training, financial inclusion, and institutional support have proven to strengthen community resilience and promote economic diversification. In addition, the integration of local cultural values into entrepreneurial practices enhances social cohesion and supports environmental sustainability. This study concludes that inclusive entrepreneurship is an important driver of long-term regional resilience and equitable development. It recommends the formulation of integrated policies that link education, local governance, and digital innovation with inclusive economic practices, while also opening directions for further empirical research on locally based entrepreneurial ecosystems.